2007
DOI: 10.1121/1.2723646
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of turbulence transition and sound radiation for flow through a rigid glottal model

Abstract: Large eddy simulation (LES)-based computational aeroacoustics techniques were applied to a static model of the human glottis, idealized here as a planar channel with an orifice, to study flow-acoustic interactions related to speech. Rigid models of both converging and diverging glottal passages, each featuring a 20 deg included angle and a minimal glottal diameter of 0.04 cm, with an imposed transglottal pressure of 15 cm H2O, were studied. The Favre-filtered compressible Navier-Stokes equations were integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 50 publications
1
23
0
3
Order By: Relevance
“…Using unsteady CFD solvers, two-dimensional, axisymmetric, and three-dimensional glottal configurations have been analyzed with and without vocal fold motion ͑Zhao et al., 2001, 2002Zhang et al, 2002;Hofmans et al, 2003;Alipour and Scherer, 2004;Decker and Thomson, 2007;Mihaescu et al, 2007;Suh and Frankel, 2007͒. In many of these numerical studies, the sound generated by the laryngeal airflow was considered ͑Zhao et al., 2001, 2002Zhang et al, 2002;Mihaescu et al, 2007;Suh and Frankel, 2007͒. Parametric studies involving the influence of Reynolds number on the flow characteristics and the effect of different divergent glottal angles on the flow separation point have also been performed ͑Zhang et al, 2002;Alipour and Scherer, 2004;Mihaescu et al, 2007͒.…”
Section: Introductionmentioning
confidence: 98%
“…Using unsteady CFD solvers, two-dimensional, axisymmetric, and three-dimensional glottal configurations have been analyzed with and without vocal fold motion ͑Zhao et al., 2001, 2002Zhang et al, 2002;Hofmans et al, 2003;Alipour and Scherer, 2004;Decker and Thomson, 2007;Mihaescu et al, 2007;Suh and Frankel, 2007͒. In many of these numerical studies, the sound generated by the laryngeal airflow was considered ͑Zhao et al., 2001, 2002Zhang et al, 2002;Mihaescu et al, 2007;Suh and Frankel, 2007͒. Parametric studies involving the influence of Reynolds number on the flow characteristics and the effect of different divergent glottal angles on the flow separation point have also been performed ͑Zhang et al, 2002;Alipour and Scherer, 2004;Mihaescu et al, 2007͒.…”
Section: Introductionmentioning
confidence: 98%
“…The authors clearly demonstrated self-sustained oscillations of the VFs; however, the grid resolution was too low to provide detailed flow field information. Suh and Frankel (2007) used the large-eddy simulation approach to simulate the compressible flow through a 3D static larynx model in order to investigate the flow-acoustic interactions during phonation. More recently, Schwarze et al (2011) developed a highly resolved, 3D computational model of the starting glottal jet flow in a channel with a static, glottisshaped constriction.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical investigations were carried out for example by Zhao et al (2002), Zhang et al (2002a), Horácek andSvec (2002, Horácek et al (2005), Krane (2005), Suh and Frankel (2007), Chouly et al (2008), Mihaescu et al (2010), Zheng et al (2011) and Smith and Thomson (2013). Experiments were performed for example by Zhang et al (2002bZhang et al ( , 2004; Zhang and Mongeau (2006); Zhang and Neubauer (2010), Krane et al (2007), Neubauer et al (2007) and Khosla et al (2007Khosla et al ( , 2008aKhosla et al ( ,b, 2009.…”
Section: Introductionmentioning
confidence: 99%